2016
DOI: 10.11606/0031-1049.2016.56.08
|View full text |Cite
|
Sign up to set email alerts
|

Influência do ciclo lunar no padrão de atividade de Cuniculus paca (Rodentia: Cuniculidae) em uma floresta de Mata Atlântica no Sul do Brasil

Abstract: InfluêncIa do cIclo lunar no padrão de atIvIdade de CuniCulus paCa (rodentIa: cunIculIdae) em uma floresta de mata atlântIca no sul do BrasIl alan deIvId pereIra¹⁴ elvIra de BastIanI² sergIo BazIlIo³ ABSTRACT Information on the activity period is relevant to understand how species adapt themselves and persist in their environment. The influence of moonlight on the activity pattern of mammals has already been reported for certain species. Ten photo-traps set during 12 months were distributed in a fragment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The activity patterns of medium and large mammals of the present work corroborated other studies for N. nasua, E. barbara, C. paca, C. brachyurus and S. brasiliensis (CIOCHETI, 2007;MICHALSKI;NORRIS, 2011;LIRA-TORRES;BRIONES-SALAS, 2012;LUNA, 2014;ROCHA, 2015;PINHEIRO, 2015;SANTIAGO, 2015;PEREIRA et al, 2016;NODARI, 2016). Cuniculus paca was classified as nocturnal, differing from the results observed by Luna (2014).…”
Section: Discussionsupporting
confidence: 90%
“…The activity patterns of medium and large mammals of the present work corroborated other studies for N. nasua, E. barbara, C. paca, C. brachyurus and S. brasiliensis (CIOCHETI, 2007;MICHALSKI;NORRIS, 2011;LIRA-TORRES;BRIONES-SALAS, 2012;LUNA, 2014;ROCHA, 2015;PINHEIRO, 2015;SANTIAGO, 2015;PEREIRA et al, 2016;NODARI, 2016). Cuniculus paca was classified as nocturnal, differing from the results observed by Luna (2014).…”
Section: Discussionsupporting
confidence: 90%
“…This information is associated with the concepts of photophobia in general and of lunar phobia in particular, a behavior attributed to species as an antipredator strategy. It has also been suggested that pacas exhibit photophobia in settings such as open fields [51] and secondary forests [52] in the Amazon, and it has been shown in an Atlantic Forest fragment in southern Brazil [53]. In primary forests in the Amazon, however, Michalski and Norris [54] did not observe a clear correlation between lunar phases and the occurrence of pacas in samplings using camera traps.…”
Section: Resultsmentioning
confidence: 99%